229k views
0 votes
Substitute x with -2

Substitute x with -2-example-1

2 Answers

0 votes

Hello from MrBillDoesMath!


Answer:

-105

Discussion:

(13-4x) (x ^2 + 5x + 1) = => substitute x = -2

(13 - 4(-2) ) ( (-2)^2 + 5(-2) + 1 ) =

(13 + 8) ( 4 -10 + 1) =

(21) ( -5) = - 105


Thank you,

MrB





User Fatemeh Abdollahei
by
5.9k points
4 votes

Answer:

-105

Explanation:

Substituting is like "plug and chug", so we can plug in -2 into the expression and get
(13 - 4(-2))((-2)^2+5(-2)+1), which simplifies into 21*-5, or -105.
\blacksquare

User Danielmhanover
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.